4.5-Year Follow-up with a Novel Corneal Endothelial Prosthesis - Lapid-Gortzak, Ruth; van der Meulen, Ivanka (Klinische Monatsblätter für Augenheilkunde, 2025)
Background Refractory corneal edema is the foremost reason for endothelial corneal transplantation (EK) in the world. Descemet membrane endothelial keratoplasty (DMEK) and Descemet stripping automated endothelial keratoplasty (DSAEK) offer good clinical outcomes. However, human donor tissue is limited in availability and has a complex logistical chain. Many patients in need do not have access to EK. Success of the human donor tissue depends on its quality, the number of rebubbles, repeat keratoplasties, and patient-related risk factors. The use of an endothelial corneal keratoprosthesis could benefit patients with a high risk for graft failure and human graft rejection, and patients in underserved areas where tissue banking is unavailable.Patients and Methods Case cohort series of 10 eyes of 10 patients implanted with the EndoArt, with a follow-up of up to 4.5 years. Outcome measures are device adherence, central corneal thickness, visual acuity, and incidence of adverse events.Results In the first seven eyes, the EndoArt was implanted in eyes with low visual potential within the first-in-human (FIH) trial, and in the three remaining eyes, implantation was performed because of either guarded posterior or anterior segment prognosis or the patientʼs wishes. In 9/10 eyes, device adherence was obtained and maintained throughout the follow-up period. Mean corneal thickness decreased from 927 + SD 241 microns to 621 + SD 140 microns. In 6/10 eyes, visual acuity improved from a mean preoperative value of logMAR 1.94 + 0.63 to a mean postoperative value of logMAR 0.8 + 0.64. No pathological thinning or corneal metabolic changes were seen. The surgical technique was developed during the follow-up period.Conclusion The EndoArt provided a stable decrease in central corneal thickness, improved vision in 60% of eyes, and had no device-related adverse events. The EndoArt is an additional treatment modality for special cases like repeat corneal graft failure in the population of the Western world, or as a primary procedure in underserved areas worldwide.
Keywords: keratoplasty; endothelial keratoplasty; corneal edema; EndoArt; keratoprosthesis